A randomised controlled trial examining the efficacy of smoking-related response inhibition training in smokers: a study protocol - Petra K. Staiger; Melissa J. Hayden; Karen Guo; Laura K. Hughes; Jason Bos; Natalia S. Lawrence (BMC, 2018)
Abstract Background Smoking is one of the leading preventable causes of illness and premature death worldwide. Despite a variety of effective treatments, relapse rates remain high, and novel, innovative interventions are needed in order to reduce the global prevalence of smoking. Research has indicated that deficits in the ability to inhibit a response (referred to as response inhibition) is a predictor of relapse and subsequently, targeting this potentially modifiable risk factor may lead to improvements in smoking outcomes. Indeed, in recent years, stimulus-specific response inhibition training has emerged as a potentially efficacious intervention to reduce unwanted/unhealthy behaviours such as alcohol and unhealthy food consumption. As such, the present trial is the first to evaluate the real-world efficacy of response inhibition smoking training (INST) in a sample of adult heavy smokers. Methods/design This randomised controlled trial will recruit nicotine dependent smokers aged between 18 and 60 using social media and advertisements in Victoria, Australia. The sample target was 150 to account for drop out and non-adherence. Once informed consent has been obtained, participants complete a range of baseline measures during a face to face interview. Participants are randomly allocated to one of two online training conditions: an intervention training group (INST), which requires participants to exercise response inhibition towards smoking-related stimuli; or an active control group, which requires participants to exercise response inhibition towards household items and does not include any smoking-related stimuli. They complete the first training session during the interview to ensure the training protocol is clear. Both groups are instructed to complete a further 13 training sessions (1 per day) at home on their computer and follow-up phone calls will be conducted at three time points: post-intervention, one-month and three months. The primary outcomes are: a) rates of smoking cessation and; b) reduction in the quantity of average daily smoking at post-intervention, one and three months follow-up. Discussion There is a pressing need to develop novel and innovative smoking interventions. If proven to be effective, INST could make a highly cost-effective contribution to improvements in smoking intervention outcomes. Trial registration The trial was prospectively registered with the Australian New Zealand Clinical Trials Registry 17th February 2017. Trial ID: ACTRN12617000252314.